Devolution is secondary: What drives Scottish secondary legislation?. (11th October 2020) - Bevan, Shaun
Abstract: The reopening of the Scottish Parliament in 1999 marked a great opportunity to create a modern government connected to the people. In spite of this, work on responsiveness and the functioning of policy‐making in Scotland since devolution has not been as extensive as it could be. This is certainly true of one of the most common and numerous policy‐making activities undertaken by Scotland and indeed all UK governments, the production of secondary legislation. This article uses time series cross‐sectional analyses to assess the effects of attention by the UK government, the EU, public priorities and the media on Scottish statutory instruments. It finds strong effects for the UK media on Scottish instruments although that effect is lower for policy areas technically, but not practically, outside the competencies of Scottish government. This work hints at a government responsive to events, but also a government that largely sets its own independent priorities.